Analsis determinan yang mempengaruhi perdagangan luar negeri Indonesa terhadap dua negara yang terlibat perang dagang Amerika Serikat VS China - Emilia, Emilia; Bhakti, Adi; Mustika, Candra (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study is to analyze how Indonesia's exports and imports compared to the United States and China and to investigate how the exchange rate, labor force, and population influence Indonesia's imports from China and the United States. The results show that Indonesia's exports to the United States and Indonesia's exports to China are 2.02, while the average comparison of Indonesian imports from the United States and Indonesia's imports from China is 1.31. the average is more significant when compared to Indonesia's exports and imports with China. Based on the regression results, the exchange rate variable has a significant negative effect on Indonesia's exports and imports with the United States and China. The labor variable has a significant positive impact on Indonesia's exports and imports to the United States and China. In contrast, the population variable significantly affects Indonesia's exports to the United States. It does not substantially affect Indonesian imports from the United States and does not dramatically affect Indonesia's exports and imports with China. Â